Premature senescence in Bt Cotton: understanding the mechanisms and control measures - Yizhen Chen; Hezhong Dong (Journal of Cotton Research)
Abstract Premature senescence in Bacillus thuringiensis (Bt) cotton has emerged as a significant challenge to the formation and realization of fiber yield and quality since its commercialization in 1997. Initially, premature senescence was thought to be an inherent trait associated with the Bt gene. However, subsequent research and practice have demonstrated that it is not directly linked to the Bt gene but rather results from a physiological imbalance between the sink and source, as well as between the root and shoot in Bt cotton. This short review provides an overview of the causes, mechanisms, and control measures for premature senescence in Bt cotton. It offers valuable insights for future research and the sustainable application of transgenic crops.